Behaviour of T-shaped RC deep beams with openings under different loading conditions. (June 2021) - Ghali, Mona K.; Said, Mohamed; Mustafa, T.S.; El-Sayed, Abdallah A.
Abstract: The shear performance of T-shaped reinforced concrete (RC) deep beams with openings and subjected to several loading types was numerically investigated; and compared with existing experimental results. The studied parameters included flange dimensions, shear span-to-depth ratio, concrete strength, size and location of openings, VL and HZ stirrups ratios and loading type. In addition, top and bottom loaded deep beams were investigated. Increasing the flange depth by 50% and 100% increases the initial cracking load by 10% and 14% and the ultimate shear capacity by 16% and 22% respectively. The opening size controlled the appearance of the first diagonal crack load. Decreasing the opening size enhanced the first cracking load. Decreasing (a/d) by 16.7% and 41.7% increased the cracking load by 17% and 131% and the ultimate shear capacity by 13% and 115% respectively. Finally, the shear capacities for 71 test results have been calculated using an existing strut-and-tie model (STM). The comparison showed that the STM model performs well in predicting the ultimate shear capacity. The overall average value of the ratio between NLFE and predicted strengths is 1.157.